2021
DOI: 10.1038/s41467-020-20711-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of telomere silencing by SESAME complex-catalyzed H3T11 phosphorylation

Abstract: Telomeres are organized into a heterochromatin structure and maintenance of silent heterochromatin is required for chromosome stability. How telomere heterochromatin is dynamically regulated in response to stimuli remains unknown. Pyruvate kinase Pyk1 forms a complex named SESAME (Serine-responsive SAM-containing Metabolic Enzyme complex) to regulate gene expression by phosphorylating histone H3T11 (H3pT11). Here, we identify a function of SESAME in regulating telomere heterochromatin structure. SESAME phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 73 publications
3
48
0
Order By: Relevance
“…Most genes can also display changes in the epigenome and chromatin organization, typically at senescence-associated heterochromatin foci (SAHF), to drive aging. These changes can be triggered by disruption of mitochondrial function, glucose metabolism and autophagy (Di Micco et al, 2021;Zhang et al, 2021).…”
Section:  Extracellular Vesicles In the Cellular Senescence And Aging Microenvironment  Cellular Senescence And The Aging Microenvironmentioning
confidence: 99%
“…Most genes can also display changes in the epigenome and chromatin organization, typically at senescence-associated heterochromatin foci (SAHF), to drive aging. These changes can be triggered by disruption of mitochondrial function, glucose metabolism and autophagy (Di Micco et al, 2021;Zhang et al, 2021).…”
Section:  Extracellular Vesicles In the Cellular Senescence And Aging Microenvironment  Cellular Senescence And The Aging Microenvironmentioning
confidence: 99%
“…Our group also showed that the yeast pyruvate kinase Pyk1 can form a complex called SESAME to phosphorylate histone H3T11 (H3pT11) to repress gene expression in response to glucose and serine availability . We also find that SESAME phosphorylates H3T11 at telomeres to maintain the integrity of telomere heterochromatin during chronological aging (Zhang et al, 2021). H3pT11 can contribute to tumorigenesis by recruiting chromatin modifying factors.…”
Section: Histone Phosphorylationmentioning
confidence: 61%
“…Total RNA was isolated from exponentially growing yeast cells by standard phenol-chloroform extraction procedures 17 . The extracted RNA was treated with RNase-free DNase I (Takara, 2270 A) and quantified by Nanodrop 2000 (Thermo scientific).…”
Section: Methodsmentioning
confidence: 99%
“…For example, glucose can be converted to acetyl-CoA, which is then fueled to histone acetyltransferases (HATs) to increase the overall histone acetylation and alter the global chromatin structure 14 , 15 . We have previously reported that glycolysis is required for pyruvate kinase-mediated histone H3 phosphorylation at threonine 11 (H3pT11) 16 , which confers cell resistance to oxidative stress and maintains normal telomere silencing 17 , 18 . Pyruvate kinase-containing SESAME complex interacts with histone acetyltransferase SAS complex to promote histone H4K16ac and maintain transcription silencing at subtelomere regions 19 .…”
Section: Introductionmentioning
confidence: 99%